Too Abstract to Be Feasible? Applying the Grounded Theory Method in Social Movement Research - Ina Peters (German Institute of Global and Area Studies (GIGA), 2014)
Grounded theory methodology (GTM) has become a popular approach in the social sciences. Based on an iterative research design and reconstructive hermeneutic procedures, it enables scholars to reveal and comprehend patterns of understanding that are reproduced through linguistic and nonlinguistic symbols. Yet the vast literature on GTM often leaves scholars wondering how the method can be operationalized. This paper serves the dual purpose of providing a precise and comprehensive review of GTM sensu Anselm Strauss and Juliet Corbin while at the same time discussing its application in a social movement research project. Done thoroughly, GTM demands high levels of reflexivity, transparency, and openness from the qualitative scholar. I propose that these requirements concern not only the sampling and data collection but also the researcher's previous assumptions, transcription, translation, and data quality. As the latter aspects are frequently neglected, the paper calls for more accuracy in the application and documentation of research methods.
Keywords: 300; qualitative research methods; grounded theory methodology (GTM); field research; semistructured interviews; foreign languages